The effect of self-efficacy and social influence on behavioral intention to use Zoom Cloud Meeting in implementing virtual learning for students of Brawijaya University - Ramadiansyah, Sahri Aflah; Safitri, Reza; Prasetyo, Bambang Dwi (Technium Social Sciences Journal, 2022)
This study discusses and analyzes the relationship between the influence of self-efficacy and social influence on the behavioral intention to use Zoom Cloud Meeting in the implementation of virtual learning for Brawijaya University students. In this study, the researcher used random sampling to take samples, namely from 100 students from various faculties. This research uses descriptive quantitative. This study uses the theory proposed by Davis, namely the Technology Acceptance Model (TAM). In this study, the researchers modified the core theoretical concepts, namely Perceiver Usefulness (PU), Perceived Easy of Use (PEOU), and Behavioral Intention to Use (BITU) by adding external variables, namely Self-Efficacy and Social Influence on the use of Zoom Cloud Meetings in virtual operations. student learning Universitas Brawijaya.